DEVELOPING INTERACTIVE LEARNING MEDIA USING GOOGLE SITES TO IMPROVE LEARNING OUTCOMES - Dwi Arini; Jasiah (World Psychology, 2026)
The rapid development of information and communication technology has driven innovation in the field of education, particularly through the utilization of digital-based learning media. One such platform that can support interactive learning is Google Sites. This study aims to develop and describe Google Sites-based interactive learning media and to analyze its role in enhancing student engagement, independence, and learning outcomes. This research employs a qualitative approach using descriptive-analytical library research. The results indicate that Google Sites offers significant advantages in terms of accessibility, flexibility, and the ability to integrate various learning resources—such as text, images, videos, and learning evaluations—into a single platform. The utilization of Google Sites as interactive learning media fosters a more engaging learning environment, boosts student activity and independence, and ultimately has a positive impact on improving learning outcomes. Consequently, Google Sites serves as an effective and relevant alternative for interactive learning media to support education in the digital era.